Reformulation, négociation et progression discursive dans le débat radiophonique. Enjeux pour le développement de l’enseignement/apprentissage de la compétence discursive - Richard, Élisabeth; Drouet, Griselda (Studia Romanica Posnaniensia, 2017)
In this article, we deal with listening comprehension skills as we would like to define it anew in light of an oral speech analysis perspective insisting on developing the communicative expertise. In order to do so, we rely on a methodology that implies observation and analysis of oral speech and that highlights the language dynamics and the multiple enunciative point of views structuring radio programme debates.